Kinerja Room Air Conditioner (RAC) Window Berdasarkan Variasi Tekanan Pengisian - Jumardi (Politeknosains, 2016)
This research was started with making the practice of media of Window Air Conditioner which will be used to teach Practice Refrigeration and Air conditioner subjects. The objective of this media was to explain the name, function, layout of the electrical and main components, R-22 circulation, evacuating the system, charging, and the working principle of the electrical system. The Media of window air conditioner was made in the Laboratory of Bench Work and Electrical Power Engineering in Politama Surakarta, which consists of the electrical and main components, and wiring diagram. The data were collected by observation, interview, and documentation. The research began by testing the system, namely: evacuating the system, then R-22 charging. The pressure of R-22 charging was varied from 23%, 38%, 45%, 55%, and 60% of the high pressure standard. The standard pressure on the window air conditioner was 4.8 bar or 70 psig with evaporation temperature 50C ( the low pressure side), and 16.3 bar or 236 psig at a temperature of 450C condensation (the high pressure side). The standard electric current in this research was 3,6A for compressor motor and 0,1A for fan motor. Data were analyzed by comparing the results of research observation with its default value, hereafter are described in percentages. Based on the research results, the system can achieve the vacuum pressure -30 in Hg within 3 minutes, and didnot experience leakage within 24 hours. The electric current on the compressor motor is proportional with increaseing charging pressure (42% - 61% of the standard current). The electric current of the fan motor in accordance with nameplate or standards, 0,1A (0%). The biggest percentage of input temperature is the evaporator (420% - 480%), then the compressor (164% - 173%), thereafter the condenser (51% - 61%) and the smallest is the capillary tube (29% - 38%). The biggest percentage of output temperature is the capillary tube (420% - 480%), then the evaporator (164% - 173%), thereafter the compressor (51% - 61%) and the smallest is the condensor (27% - 32%).The working principle of the media of window air conditioner consists of five positions, namely: Off, Fan, Super Quiet, Normal, and High Power.